2016
DOI: 10.5489/cuaj.3301
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy With One Shot Dilatıon Method: Is It Safe In Patients Who Had Open Surgery Before

Abstract: Introduction: This study aimed to evaluate whether one-shot dilatation technique is as safe in patients with a history of open-stone surgery as it is in patients without previous open-stone surgery. Methods: Between January 2007 and February 2015, 82 patients who underwent percutaneous nephrolithotomy (PNL) surgery with one-shot dilation technique who previously had open-stone surgery were retrospectively reviewed and evaluated (Group 1). Another 82 patients were selected randomly among patients who had PNL wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition, the presence of staghorn stones in these two patients is a risk factor for bleeding. [19] However, in their study comparing OD procedure in cases undergoing primary intervention and secondary intervention, Süelözgen et al [23] reported no difference between the groups concerning bleeding complications. Considering these major complications, it should be re-emphasized that PCNL has a significant complication potential, regardless of the dilatation technique used.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the presence of staghorn stones in these two patients is a risk factor for bleeding. [19] However, in their study comparing OD procedure in cases undergoing primary intervention and secondary intervention, Süelözgen et al [23] reported no difference between the groups concerning bleeding complications. Considering these major complications, it should be re-emphasized that PCNL has a significant complication potential, regardless of the dilatation technique used.…”
Section: Discussionmentioning
confidence: 98%
“…10 There are previous studies demonstrated that using larger sheath, longer operation duration, and multiple tracts increase renal bleeding complication rate in PNL operations, as well as some other studies reported that these factors have no effect on renal bleeding complication rates. 6,8,10,11 In a study comparing the effects of renal access techniques on bleeding complications, balloon dilatation method was reported to cause less bleeding than the amplatz dilation method. 12 The high cost of balloon dilators is limiting their use.…”
Section: Discussionmentioning
confidence: 99%
“…The tract was dilated by Teflon dilators (gradual or acute) up to 24-26 French. Acute dilatation is defined as one-shot dilatation (12). Nephroscope 26 Fr with outer sheath, 24 Fr without the outer sheath, and pneumatic disintegrator were used.…”
Section: Methodsmentioning
confidence: 99%